The Relationship between Individual Factors and Occupational Factors with the Risk of LBP (Low Back Pain) in Workers at the Jakarta Provincial Health Office - Aprilia, Savira; Setianingsih, Ajeng; Rafida, Neni Herlina (Jurnal Kesehatan Masyarakat Perkotaan, 2025)
According to the World Health Organization (WHO) in 2023, LBP (Low Back Pain) is the number one cause of disability in the world, with 619 million sufferers in 2020 and is estimated to increase to 843 million cases in 2050. LBP is often experienced by workers due to non-ergonomic working positions, long working hours, and repetitive activities. This complaint can be caused by various factors, both identifiable and unidentifiable. This study aims to determine the relationship between individual factors (age and gender) and work factors (work position, work period, work duration, and repetition) with the incidence of LBP in employees of the DKI Jakarta Provincial Health Office in 2025. This study used a cross-sectional design with 63 respondents selected through a total sampling technique. The research instrument was a questionnaire whose validity and reliability had been tested using the Chi-Square test at the 95% level. The results of the study showed that individual factors in the form of age and gender and work factors in the form of work duration were not related to the occurrence of LBP, while work factors in the form of work position, work period, and repetitive activities were related to the occurrence of LBP. Research recommendations include efforts to maintain spinal health by paying attention to body position while working, implementing short stretches at certain hours, the 20-20-20 rule, and the preparation of formal regulations in the form of SOPs, SKPs, or Circular Letters to prevent LBP on an ongoing basis.